21st‐Century Water Meters Maximize Precision. Issue 4 (6th May 2021) - Crevcoure, Brooke; Weston, Tasha
Abstract : Water meters determine the success of any water system. Today's smart, long‐lasting meters have raised the bar on technology that has evolved dramatically in the past decade.